Routine sterile glove and instrument change at the time of abdominal wound closure to prevent surgical site infection (ChEETAh): a pragmatic, cluster-randomised trial in seven low-income and middle-income countries. Issue 10365 (19th November 2022) - ; Ademuyiwa, Adesoji O; Adisa, Adewale O; Bhangu, Aneel; Brocklehurst, Peter; Chakrabortee, Sohini; Ghosh, Dhruva; Glasbey, James; Haque, Parvez D; Hardy, Pollyanna; Harrison, Ewen; Ingabire, JC Allen; et al.
Summary: Background: Surgical site infection (SSI) remains the most common complication of surgery around the world. WHO does not make recommendations for changing gloves and instruments before wound closure owing to a lack of evidence. This study aimed to test whether a routine change of gloves and instruments before wound closure reduced abdominal SSI. Methods: ChEETAh was a multicentre, cluster randomised trial in seven low-income and middle-income countries (Benin, Ghana, India, Mexico, Nigeria, Rwanda, South Africa). Any hospitals (clusters) doing abdominal surgery in participating countries were eligible. Clusters were randomly assigned to current practice (42) versus intervention (39; routine change of gloves and instruments before wound closure for the whole scrub team). Consecutive adults and children undergoing emergency or elective abdominal surgery (excluding caesarean section) for a clean–contaminated, contaminated, or dirty operation within each cluster were identified and included. It was not possible to mask the site investigators, nor the outcome assessors, but patients were masked to the treatment allocation. The primary outcome was SSI within 30 days after surgery (participant-level), assessed by US Centers for Disease Control and Prevention criteria and on the basis of the intention-to-treat principle. The trial has 90% power to detect a minimum reduction in the primary outcome from 16% to 12%, requiring 12 800 participants from at least 64 clusters. The trial was registered with ClinicalTrials.gov, NCT03700749 . Findings: Between June 24, 2020 and March 31, 2022, 81 clusters were randomly assigned, which included a total of 13 301 consecutive patients (7157 to current practice and 6144 to intervention group). Overall, 11 825 (88·9%) of 13 301 patients were adults, 6125 (46·0%) of 13 301 underwent elective surgery, and 8086 (60·8%) of 13 301 underwent surgery that was clean–contaminated or 5215 (39·2%) of 13 301 underwent surgery that was contaminated–dirty. Glove and instrument change took place in 58 (0·8%) of 7157 patients in the current practice group and 6044 (98·3%) of 6144 patients in the intervention group. The SSI rate was 1280 (18·9%) of 6768 in the current practice group versus 931 (16·0%) of 5789 in the intervention group (adjusted risk ratio: 0·87, 95% CI 0·79–0·95; p=0·0032). There was no evidence to suggest heterogeneity of effect across any of the prespecified subgroup analyses. We did not anticipate or collect any specific data on serious adverse events. Interpretation: This trial showed a robust benefit to routinely changing gloves and instruments before abdominal wound closure. We suggest that it should be widely implemented into surgical practice around the world. Funding: National Institute for Health Research (NIHR) Clinician Scientist Award, NIHR Global Health Research Unit Grant, Mölnlycke Healthcare.